Cytomorphological Changes in the Hepate of the White Sea Coastal Cod (Gadus morhua maris-albi Derjugin, 1920) during Parasitic Invasions - Shakurova N.V.; Kudryavtseva E.V. (Учёные записки Казанского университета: Серия Естественные науки)
The cod Gadus morhua maris-albi is one of the most heavily infested fish species in the White Sea. The fish liver (hepate) is a convenient model to study the pathogenesis in parasitosis. A transmission electron microscopy study of the White Sea cod hepatocytes in both minor and severe infestation was performed in this paper. The ultrastructure of hepatocytes and pericytes in minor infestation was analyzed. The signs of fatty liver disease in specimens with the high degree of infestation were revealed. Changes in the fine structure of hepatocytes and adaptation of the organism to parasitosis were discussed.